Computing and mathematical modeling - Thangavel, K. : | Balasubramaniam, P. (Narosa New delhi, 2006)
Mathematics is the common language of modern Science, Engineering, and Business. This volume discusses pioneering methods and applications, which precipitate the solution of complex problems - or even make such solutions possible at all.
Cryptography -- Data mining -- Image processing -- Mechanical modeling -- Neural network -- Operations research -- Theory of computation.
Keywords: Computer algorithms | Numerical analysis | Mathematical models | Mathematics -- Data processing